Characterization of the "deqi" response in acupuncture - Rosen Bruce R; Hodge Steven M; Napadow Vitaly; Marina Ovidiu; Liu Jing; Vangel Mark G; Nixon Erika E; Hui Kathleen KS; Makris Nikos; Kennedy David N (BMC Complementary and Alternative Medicine, 2007)
Abstract Background Acupuncture stimulation elicits deqi, a composite of unique sensations that is essential for clinical efficacy according to traditional Chinese medicine (TCM). There is lack of adequate experimental data to indicate what sensations comprise deqi, their prevalence and intensity, their relationship to acupoints, how they compare with conventional somatosensory or noxious response. The objective of this study is to provide scientific evidence on these issues and to characterize the nature of the deqi phenomenon in terms of the prevalence of sensations as well as the uniqueness of the sensations underlying the deqi experience. Methods Manual acupuncture was performed at LI4, ST36 and LV3 on the extremities in randomized order during fMRI in 42 acupuncture naïve healthy adult volunteers. Non-invasive tactile stimulation was delivered to the acupoints by gentle tapping with a von Frey monofilament prior to acupuncture to serve as a sensory control. At the end of each procedure, the subject was asked if each of the sensations listed in a questionnaire or any other sensations occurred during stimulation, and if present to rate its intensity on a numerical scale of 1–10. Statistical analysis including paired t-test, analysis of variance, Spearman's correlation and Fisher's exact test were performed to compare responses between acupuncture and sensory stimulation. Results The deqi response was elicited in 71% of the acupuncture procedures compared with 24% for tactile stimulation when thresholded at a minimum total score of 3 for all the sensations. The frequency and intensity of individual sensations were significantly higher in acupuncture. Among the sensations typically associated with deqi, aching, soreness and pressure were most common, followed by tingling, numbness, dull pain, heaviness, warmth, fullness and coolness. Sharp pain of brief duration that occurred in occasional subjects was regarded as inadvertent noxious stimulation. The most significant differences in the deqi sensations between acupuncture and tactile stimulation control were observed with aching, soreness, pressure and dull pain. Consistent with its prominent role in TCM, LI4 showed the most prominent response, the largest number of sensations as well as the most marked difference in the frequency and intensity of aching, soreness and dull pain between acupuncture and tactile stimulation control. Interestingly, the dull pain generally preceded or occurred in the absence of sharp pain in contrast to reports in the pain literature. An approach to summarize a sensation profile, called the deqi composite, is proposed and applied to explain differences in deqi among acupoints. Conclusion The complex pattern of sensations in the deqi response suggests involvement of a wide spectrum of myelinated and unmyelinated nerve fibers, particularly the slower conducting fibers in the tendinomuscular layers. The study provides scientific data on the characteristics of the 'deqi' response in acupuncture and its association with distinct nerve fibers. The findings are clinically relevant and consistent with modern concepts in neurophysiology. They can provide a foundation for future studies on the deqi phenomenon.